Study protocol for a randomised-controlled study on emotion regulation training for adolescents with major depression: the KONNI study - Ellen Greimel; Lisa Feldmann; Charlotte Piechaczek; Frans Oort; Jürgen Bartling; Martin Schulte-Rüther; Gerd Schulte-Körne (BMJ Open)
Introduction Major depression (MD) often has its onset during adolescence and is associated with significant morbidity and mortality. One important factor for the development and maintenance of adolescent MD are disturbances in emotion regulation and the underlying neural processes. Cognitive reappraisal (CR) is a particular adaptive emotion regulation strategy. Previously, it has been shown in healthy adults that a task-based training in CR is efficient to reduce negative affect, and that these effects translate into everyday life.This randomised controlled trial examines for the first time whether a task-based training in CR proves effective in MD adolescents. Specifically, we will investigate whether the CR training improves the ability to downregulate negative affect in MD individuals as assessed by behavioural and neurobiological indices, and whether training effects generalise outside the laboratory.Methods and analysis Adolescents with MD will be randomly allocated to a group that either receives a task-based training in CR or a control training. Both involve four training sessions over a time period of 2 weeks. In the CR training, participants will be instructed to downregulate negative affective responses to negative pictures via CR, while the control training involves picture viewing. During the training sessions, the Late Positive Potential, gaze fixations on negative picture aspects and affective responses to pictures will be collected. Before and after the training programmes, and at a 2-week follow-up, overall negative and positive affect, rumination and perceived stress will be assessed as primary outcomes. Analyses of variance will be conducted to test the effectiveness of the CR training with regard to both primary outcomes and task-based behavioural and neurobiological parameters.Ethics and dissemination The study was approved by the Ethics Committee of the Medical Faculty of the LMU Munich, Germany. The results will be published in peer-reviewed journals and disseminated through conferences, social media and public events.Trial registration details ClinicalTrials.gov NCT03957850, registered 21st May 2019; URL: https://clinicaltrials.gov/ct2/show/NCT03957850.